(untitled) (Medico Legal Update, 2020)
Introduction: Meningioma is the very important type of tumor that occur in central nervous system (CNS) that represented 1/3 of whole tumor of CNS. In USA 97/100,000, persons recorded have meningioma. With 170,000 patients detected as meningioma. The aim of study is the aim of the present study is to evaluate the use of immunhistochemical expression of PR and ki67 for predicting the grades of meningioma, which are important in their prognosis, and line of treatment. Method: Ninety patients with meningioma were collected from the Neurosurgical Hospital-Baghdad, during the period from January 2017 to January 2020. The data for cases were collected to study the age, gender and grade of tumor. Staining hematoxylin/Eosin (H plus E) for histological inputting and classifying of the tumors and immunohistochemically workup for PR & Ki67 done. Results: Cross sectional study for 90 patients with age, mean (44 ± 12) years old, in current study 64% of patients was females and 36% of patients was males, strong positive PR expression represented 50% of patients, 79% of patients have low Ki 67, 15% of them have intermediate Ki67 and 6% of patients with high Ki67. Most of patients with age group 40-59 years old (51%). The mean and SD of Ki67 in (%) according to grades of meningioma I, II and III as following: (0.3 ± 0.07), (7 ± 5.9) and (38 ± 0.07) respectively. There is significant association between grades of meningioma and PR expression; 71% of grade I with PR expression strongly positive, 23% of grade II with PR expression were weakly positive and 100% of grade III with PR expression were negative. In addition, there is significant association between grades of meningioma and prognosis; 100% of grade I with good prognosis, 100% of grade II with fair prognosis and 100% of grade III with poor prognosis. In current study, also there is significant association between grades of meningioma and Ki67; 100% of grade I with low level of Ki67, 100% of grade III with high level of Ki67 and 64% of grade II with intermediate level of Ki67. There is no significant association between age and gender with grades of meningioma. Conclusion: The mean Ki-67 was significantly more in meningioma grade III than in patients with grades II and I as WHO classification. There is strong expression of PR was found mainly in the grade I typical meningioma group. Utilization of markers for proliferation (ki-67 labeling index) and hormonal expression (Progesterone Receptor) in combination with histopathological features may help in the identification of biologically aggressive meningioma.